Microalbuminuria in HIV infection - Lynda A. Szczech; Carl Grünfeld; Rebecca Scherzer; Jesse Canchola; Charles van der Horst; Stephen Sidney; David A. Wohl; Michael G. Shlipak (2007)
Microalbuminuria is associated with increased risk of cardiovascular disease and mortality. The objective of the study was to evaluate if HIV infection was an independent risk factor for microalbuminuria.Cross sectional.The relationship between HIV infection and microalbuminuria was assessed using subjects enrolled in the study of Fat Redistribution and Metabolic Change in HIV Infection, which consists of HIV-positive and control men and women. Participants with proteinuria (dipstick >or= 1+) were excluded.Microalbuminuria (urinary albumin/creatinine ratio, ACR > 30 mg/g) was present in 11% of HIV infected, and 2% of control participants (P < 0.001); a fivefold odds after multivariate adjustment (odds ratio, 5.11; 95% confidence interval, 1.97-13.31; P=0.0008). Several cardiovascular risk factors were associated with higher ACR in HIV participants: insulin resistance (HOMA > 4; 32%, P < 0.0001), systolic blood pressure (21%, P = 0.01 for 120-140 versus < 120 mmHg, and 43%, P = 0.06 for > 140 versus < 120 mmHg), and family history of hypertension (17%, P = 0.03). Higher CD4 cell count was associated with lower albumin/creatinine ratio (-24%, P = 0.009 for 200-400 versus < 200 cells/ml and -26%, P = 0.005 for > 400 versus < 200 cells/ml).HIV infection had a strong and independent association with microalbuminuria, the severity of which was predicted by markers of insulin resistance, hypertension, and advanced HIV infection. These associations warrant further investigation, as the increased prevalence of microalbuminuria in HIV infection may be a harbinger of future risk of cardiovascular and kidney diseases.